Transforming Islamic Education Management in the Era of Artificial Intelligence - Mambaul Ulum; Ilham Pebrian (Journal of Education and Learning Sciences, 2026)
This study aims to analyze the transformation of Islamic education management, identify implementation challenges, and formulate an AI-based integrative model aligned with the values of Islamic education. This research employed a library research approach, with data collected through a comprehensive review of scholarly literature published in reputable academic journals. The data were analyzed using content analysis to identify patterns, concepts, and interrelationships among the research variables. The findings reveal that the transformation of Islamic education management is not merely technological in nature, but also requires the integration of AI-based systems with spiritual values, ethics, and humanism. AI contributes to enhancing efficiency, improving decision-making effectiveness, and advancing the quality of educational services through systematic data utilization. However, its implementation continues to face several challenges, including limited human resources, inadequate digital infrastructure, and resistance within organizational culture. This study proposes an integrative model that connects technology, management functions, and Islamic educational values within a unified system. Theoretically, this research enriches the discourse on technology-based Islamic education management. Practically, the findings may serve as a reference for educational administrators in designing digital transformation strategies. Nevertheless, this study is limited by its conceptual approach; therefore, further empirical research is required to examine and validate the proposed model.